Review of the teacher training program in "Educational Inclusion." : A curriculum limited to the possibilities - Rangel Romero, Juan Carlos (Emerging Trends in Education, 2021)
Review of the  2018 educational program aimed at the training of teachers in educational inclusion by the Secretaría de Educación Pública in Mexico.